Etika dan Legalitas Pemanfaatan Tanah Jaminan dalam Hukum Islam saat Terjadi Wanprestasi - Nurifatul Jannah; Ari Kartiko (Santara: Journal of Islamic Law and Humanity, 2025)
This study discusses the utilization of collateral land due to default from an Islamic legal perspective, with a case study in Kertagena Dajah Village. The main problems studied are: (1) how the practice of utilizing collateral land due to default occurs in the village, and (2) how Islamic law reviews the practice. The purpose of this study is to analyze the suitability of the utilization of collateral land due to default with the principles of Islamic law. This study uses a qualitative method with a field study approach, relying on primary data obtained through interviews with parties directly involved in the practice of debt compensation using land as collateral, as well as secondary data from related documents and literature. The results of the study indicate that the practice of utilizing collateral land as a form of default resolution has become a habit in the Kertagena Dajah Village community, although it is carried out without a strong legal basis and without a valid written agreement according to sharia. In an Islamic legal review, this practice is considered invalid because it contains elements of injustice and potential usury. The use of collateral in this case land without a clear ijarah or compensation agreement is contrary to sharia principles, especially in terms of the prohibition of taking advantage of other people's property without legal rights. Therefore, this practice cannot be justified either normatively in Islam or ethically.